Semantic Transparency and Number Marking in Arabic and Other Languages - Kaye, Alan S. 1944-2007 (2005)
Every language has its share of odd or idiosyncratic words, expressions, idioms, and collocational ranges for its vocabulary. For example, Arabic has many lexemes, phrases and expressions which use the plural, but which translate into English in the sg. The plural in the datum in question is overtly marked in Arabic, and what it refers to can be explained in terms of the notion of a semantically transparent plurality; e.g., Gilmu llahajaat (science/NOM/the dialect/PL) ‘the science of dialects’ = ‘dialectology’. Semantic transparency can be defined as a literal cognitive mapping of an idea, thought or concept, or as ‘guessability’ for the native speaker. Thus, ‘eye doctor’ is semantically transparent, since native speakers know the meanings of ‘eye’ and ‘doctor’; however, ‘ophthalmologist’ is semantically opaque since its morphemic parts are not readily discernable. Returning to the notion of ‘dialectology’, from the viewpoint of the logic of semantic and cognitive structure, ‘dialectology’ studies dialects, usually many dialects — not merely one, and thus the marking of the plural makes logical sense. In other words, the Arabic plural marking instantaneously denotes reference to numerous dialects (in the plural!) — the object of the study of dialectology.